Cost Estimate of Early Stage forBuilding Construction in Ternate City UsingRegression Methods - EDWARD RIZKY AHADIAN; Muhamad Rizal (ICETIA, 2016)
The cost is one of the main factors because it involves the capital that would have to come out in the implementation of a construction project, a successmeasure of the constructionproject.An early cost estimation done at the conceptual stage of a projectcycle known as a conceptual estimate cost that can bedefined as a costestimate that do based on the buildingconcept will be built.An early cost estimate required by a thorough investigation into a construction project in order to provide the cost as early as possible that necessary so can take the decision or policy and plotting as good as, considering the condition of the Ternate City that having limited budget.This research is using quantitative method research, done by the statisticsapproach (regression analysis) onresearch variables with the link relations the development cost building with parameters from the concept of the building will be built.The research results show that from the result of statisticstesting obtained linearequation Y = -1,677E9 + 4.214.311,110X1with Y is the development cost building and X1is floor area of a building. And have the determinationcoefficients (r2) as much as 0,852.The results of the validation model shows that results gained by use the model chosen than the constructioncost, varying from -6,14% until +3,05%.Variation what happened to the development cost building in Ternate City can be explained by broad floor of a building and indicated the bigger floor area of a building construction of a building, so would tend to the budget that needed to construct a building